Correlation of Knowledge and Attitude of Food Handlers with The Implementation of Sanitation Hygienen in Enthong Mas Catering - Shafa Kamila Rivani; Natalia Desy Putriningtyas (Universitas Darussalam Gontor, 2023)
Background: food is a basic need every day for humans to survive on this earth. However, there are still extraordinary incidents of food poisoning caused by the application of poor hygiene and sanitation by food handlers. The Province of the Special Region of Yogyakarta ranks 11th as the province with the most cases of Extraordinary Food Poisoning (KLB KP) in Indonesia in 2021. Objective: analyze the relationship between the knowledge and attitudes of food handlers and the application of sanitary hygiene in Enthong Mas Catering. Method: quantitative study with a cross-sectional design. The sampling technique used total sampling 22 food handlers in the kitchen of Enthong Mas Catering and the dining room of the STPN Yogyakarta dormitory. The instrument in this study was a questionnaire. Data were analyzed by Fisher's test. Results: food handlers who are classified as having good knowledge (59.09%) and good attitudes (54.54%) dominate more than those who do not. Based on the Fisher test, that p-value = 0.011 <0.05, which means that there is a significant relationship between knowledge and the application of sanitary hygiene. Based on the Fisher test, that p-value = 0.004 <0.05, which means that there is a significant relationship between attitudes and the application of sanitary hygiene. Conclusion: there is a significant relationship between the knowledge and attitudes of food handlers and the application of sanitary hygiene. Age, education, and working period of food handlers have no effect on the application of sanitary hygiene. Key words : attitude, food handlers, knowledge, sanitation